Tribological and conductive behavior of Cu/Cu rolling current-carrying pairs in a water environment. (March 2020) - Sun, Yixiang; Song, Chenfei; Liu, Zili; Li, Jiawei; Wang, Li; Sun, Chao; Zhang, Yongzhen
Abstract: The effect of water on rolling current-carrying contact pairs was investigated using a disc–disc rolling tribometer in a water-dripping condition. The coefficient of friction increased with applied current and peaked over 1.1 when the current was 1.5 A, which was much higher than that recorded in air. SEM and optical microscopy demonstrated that this high coefficient of friction resulted in pits on surface and plastic flow in subsurface. XPS results indicated that CuO was generated during current-carrying rolling through two mechanisms: tribo- and electro-oxidation reactions. AFM observations suggested that the formation of oxides could weaken the conductivity of rolling pairs. These results may provide a deeper understanding on the joint effects of mechanics and chemistry on current-carrying surfaces. Highlights: Water sensitivity of current-carrying rolling contact was tested in open air. Plastic flow was observed beneath the rolling surface because of the additional shear effect of high coefficient of friction. XPS results indicate that both tribochemical and electrochemical oxidation could occur on the current-carrying surface. The conductivity of current-carrying contact pairs was weakened by surface oxidation.